First report of concomitant pheochromocytoma and duodenal neuroendocrine tumour in a sporadic multiple endocrine neoplasia type 1. (4th September 2018) - Motazedi, Banafsheh; Rahmani, Maziar; Welch, James M; Motazedi, Abbas
Abstract : A 77-year-old woman was diagnosed with pheochromocytoma followed by adrenalectomy at age 57. Hyperparathyroidism without osteoprosis was diagnosed at age 58. At age 75, Dual Energy X-ray Absoptiometry (DEXA) revealed osteoporosis and sestamibi scan showed a left parathyroid adenoma. Criteria for parathyroidectomy were met, and she underwent parathyroidectomy. Furthermore, she presented with haematochezia at age 75. An abdominal CT demonstrated a mass in the second portion of the duodenum. Additionally, octreoscan revealed somatostatin receptor positive tissue in the duodenum and Gallium 68 dotatate scan also showed a well-differentiated duodenal neuroendocrine tumour (NET). Genetic testing for MEN1, MEN2 and MEN4 was negative. Diagnosis of sporadic MEN1 syndrome was made. The patient underwent resection of the duodenal NET at age 76. She is in good health 21 years after her first presentation of MEN1. In summary, we present the first sporadic case of MEN1 with concomitant pheochromocytoma and duodenal NET which occurred 20 years apart.